2020
DOI: 10.1002/fes3.254
|View full text |Cite
|
Sign up to set email alerts
|

Rural livelihood diversity and its influence on the ecological intensification potential of smallholder farms in Kenya

Abstract: Smallholder farmers represent the majority of food producers around the world, yet they are often the most at risk of suffering yield gaps and not achieving their production potential. Ecological Intensification (EI) is a knowledge intensive approach to sustainable agricultural intensification which utilizes biodiversity‐based ecosystem services to support greater yield and reduce reliance on agrochemical inputs. Despite the potential benefit of EI based practices, uptake by smallholders is not as widespread a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…Guarín et al (2020) found that farming types with organic certifications are linked to more formal market channels. Similarly, Kansiime et al (2021) found that market-oriented farming types are more likely to make intensive use of pesticides, which is consistent with our results for Type-III, IV and V systems which are more dependent on farm income and use pesticides to ensure high production yields. Our results for Type II also seem to be consistent with Mutyasira (2020) who states that farming types located closer to markets have greater potential for crop diversification and high-value commercialisation.…”
Section: Typology Categorisationsupporting
confidence: 91%
See 2 more Smart Citations
“…Guarín et al (2020) found that farming types with organic certifications are linked to more formal market channels. Similarly, Kansiime et al (2021) found that market-oriented farming types are more likely to make intensive use of pesticides, which is consistent with our results for Type-III, IV and V systems which are more dependent on farm income and use pesticides to ensure high production yields. Our results for Type II also seem to be consistent with Mutyasira (2020) who states that farming types located closer to markets have greater potential for crop diversification and high-value commercialisation.…”
Section: Typology Categorisationsupporting
confidence: 91%
“…Moreover, our Type-II farming system supports evidence from Masi et al (2021) and Teixeira et al (2018) who found that agroecological principles are associated with farming types led by women. In terms of the variables used to measure the sustainability level of agricultural practices, we used similar variables to those found in prior studies focused on the importance of including environmental sustainability aspects in farming typologies, namely, the use of pesticides, the amount of nitrogen released, the preservation of native flora and fauna and the use of manure (Berre et al, 2019;Bánkuti et al, 2020;Kansiime et al, 2021;Stylianou Chapter 3 et al, 2020). However, our study differs from the others by using a farm-level index that aggregates the different sustainability variables (Table 3.2), making it easier to operationalise the sustainability concept and understand the complex dynamics between sustainability and farming systems.…”
Section: Typology Categorisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings show that low-resourced farm types allocated more land to crop production compared to animal grazing. Kansiime et al [53] found in Kenya that low-resourced smallholders allocated substantially more acreage to crop production than high-resourced ones. Similarly, smallholders allocated about 0.57 ha to pigeon pea farming, with an average productivity of 380 kgha −1 .…”
Section: Resource Endowment Household Characteristics and Heterogeneitymentioning
confidence: 99%
“…Transitioning from a conventional to a more IPM-based agricultural approach can be limited by, among other things, a lack of knowledge of appropriate and effective tools as well as presenting economic risks for those producers who have somewhat limited uptake and expansion potential (Alwang et al, 2019;Deguine et al, 2021;Kansiime et al, 2021). The effective contribution of natural enemies to help control pests through conservation biocontrol (CBC) is fundamental to successful IPM schemes in open systems but there is a clear lack of evidence for the potential for CBC based approaches to deliver agronomic and economic benefits for growers, with research endpoints limited primarily to effects on abundance of pests and natural enemies (Kleijn et al, 2019;Johnson et al, 2021;Girling et al, 2022).…”
Section: Introductionmentioning
confidence: 99%